Evaluation of Blood Components Logistics to Wards, Blood Transfusion Center, Faculty of Medicine, Khon Kaen University - Tantanapornkul, Puthida; Junta, Ninnate; Wanitpongpun, Chinadol; Samahadthai, Wichai (Srinagarind Medical Journal, 2025)
Background and Objective: The logistics for blood component were established at the Blood Transfusion Center, Faculty of Medicine, Khon Kaen University, from October to December 2016, and this model has been implemented in all wards to date. This study aimed to analyze the logistics outcomes for blood components using retrospective data from January 1 to July 31, 2024 Methods: A retrospective descriptive study on the provision of blood components to the wards was under taken at Srinagarind Hospital, Faculty of Medicine, Khon Kaen University. The data analysis employed descriptive statistics. Results: The blood component logistics data indicated that out of 14,698 delivery cycles, 17,305 units of red blood cells and 13,286 units of plasma were supplied Thawed plasma constituted 53.0% of 7,112 unit. The temperature control in 5,649 was delivered at 1-10oC, determined to be fully operational. The average satisfaction rate was 93.48%±1.03%. The five wards with the greatest delivery rates were emergency operations, cardiac and vascular surgery, medicine, pediatrics, and surgical critical cave unit, respectively. Conclusion: The logistics of blood components developed, totaling 30,588 units of red blood cells and plasma across 14,698 delivery cycles during a seven-month follow-up review. The temperature during shipping was effectively maintained between 1-10oC in compliance with established standards.